Wheat Germ Supplementation Increases Lactobacillaceae and Promotes an Anti-inflammatory Gut Milieu in C57BL/6 Mice Fed a High-Fat, High-Sucrose Diet. Issue 7 (4th June 2019) - Ojo, Babajide A; O'Hara, Crystal; Wu, Lei; El-Rassi, Guadalupe Davila; Ritchey, Jerry W; Chowanadisai, Winyoo; Lin, Dingbo; Smith, Brenda J; Lucas, Edralin A
ABSTRACT: Background: A link between high-fat diet consumption and obesity-related diseases is the disruption of the gut bacterial population, which promotes local and systemic inflammation. Wheat germ (WG) is rich in bioactive components with antioxidant and anti-inflammatory properties. Objective: The aim of this study was to investigate the effects of WG supplementation in modulating the gut bacterial population and local and systemic inflammatory markers of mice fed a high-fat, high-sucrose (HFS) diet. Methods: Six-week-old male C57BL/6 mice were randomly assigned to 4 groups ( n = 12/group) and fed a control (C; 10% kcal fat, 10% kcal sucrose) or HFS (60% kcal fat, 20% kcal sucrose) diet with or without 10% WG (wt:wt) for 12 wk. Cecal bacteria was assessed via 16S rDNA sequencing, fecal short-chain fatty acids by GC, small intestinal CD4 + lymphocytes using flow cytometry, and gut antimicrobial peptide genes and inflammatory markers by quantitative polymerase chain reaction. Statistical analyses included Kruskal–Wallis/Dunn's test and 2-factor ANOVA using HFS and WG as factors. Results: There was a 4-fold increase ( P = 0.007) in the beneficial bacterial family, Lactobacillaceae, in the HFS + WG compared with the HFS group. Fecal propionic and n -butyric acids were elevated at least 2-fold in C + WG compared with the other groups ( P < 0.0001). WG tended to increase (≥7%; P -trend = 0.12) small intestinal regulatory T cell:Th17 ratio, indicating a potential to induce an anti-inflammatory gut environment. WG elevated (≥35%) ileal gene expression of the anti-inflammatory cytokine Il10 compared to the unsupplemented groups ( P = 0.038). Ileal gene expression of the antimicrobial peptides Reg3b and Reg3g was upregulated (≥95%) in the HFS + WG compared with other groups ( P ≤ 0.040). WG reduced serum concentrations of the pro-inflammatory cytokines, interleukin (IL)-1B, IL-6, interferon-γ, and tumor necrosis factor-α (≥17%; P ≤ 0.012). Conclusions: WG selectively increased gut Lactobacillaceae, upregulated ileal antimicrobial peptides, and attenuated circulating pro-inflammatory cytokines of C57BL/6 mice fed a HFS diet. These changes may be vital in preventing HFS diet-induced comorbidities.